Optimalisasi Pembiasaan Membaca Al-Qur’an Dalam Membentuk Karakter Religi Madin Miftahul Ulum Kesugihan Pulung Ponorogo - Khilma Wildana Rustamil Ulumi; Diyan Putri Ayu (Social Science Academic, 2025)
Religious character is the most important chatacter that must be developed in children as eariy as possible,because religious teachings are fundamental to every individual,community,nation and state life,especially inindonesia. This service activity is carried out at the Madrasah Diniyah Miftahul Ulum Kesugihan, Pulung, Ponorogo. This study uses a method consisting of inculturation,discovery, desing, devine, and reflection activities.data collected through interviews, observation and documentation. This study aims to improve reading of the Al-Qur’an and improve religious character. Based on the results of the Research,it shows that children are able to read the Qur’an and have good and correct character according to the syariat